Morbidité Des Enfants En Zones Urbaines Africaines. Le Cas De L’observatoire De Population De Ouagadougou (Burkina Faso) - Djourdebbé, Franklin Bouba; Dos Santos, Stéphanie; Legrand, Thomas K.; Soura, Abdramane Bassiahi (European Scientific Journal, ESJ, 2018)
Rapid urbanization and its consequences in regard to access to water, sanitation, and waste management in African cities can be synonymous to health problems. Based on the data obtained from the Ouagadougou Health and Demographic Surveillance System, this paper focuses on characterizing most of those at risk of disease (fever, diarrhea, cough, infections of the skin and eyes). Spatial analysis show that populations in formal (zoned) neighbourhoods, compared to those in informal neighbourhoods, are most at risk of disease. However, in performing multiple correspondence factor analysis and classification, we found that the informal neighbourhoods are mostly at risk of disease. The formal and informal opposition is not absolute, but the differences remain strong despite the existence of atypical neighbourhoods. The contribution of the paper is to provide a new perspective for thinking in regards to the links between environment and children’s health.